EFEKTIVITAS MODEL PEMBELAJARAN STEM DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 1 GUYANGAN - Pandu Ahmad Sanubari Pandu Sejati; Fine Reffiane; Wawan Priyanto (LPPM Universitas Cipta Mandiri, 2024)
The background of this research is the lack of innovative learning and the use of learning media, so that it does not attract students' attention which results in students not being actively involved in learning and student learning outcomes being low. This type of research is quantitative. This research design uses PreExperimental Design in the form of One Group Pretest Posttest Design. The population in this study were fourth grade students at SDN 1 Guyangan. The sample used was class IV students at SDN 1 Guyangan consisting of 30 students. In this research, data was collected through observation, interviews, tests and documentation. In the initial analysis, the normality test was used to analyze the data. The final analysis uses the normality test, hypothesis test, and learning completeness test. Students showed average learning outcomes of 50.13% without the STEM learning model (pretest), and 80.93% after treatment with the STEM learning model (posttest). This is reinforced by the results of the paired t-test calculation that the significance value produced by the paired t-test on the pretest and posttest results is 0.001 < 0.05, so H0 is rejected and Ha is accepted, and it can be concluded that the STEM learning model is effective for improving student learning outcomes. in science and science learning in class IV SDN 1 Guyangan.